조영제 혈관 외 유출이 관찰된 복부 둔상 환자의 유출부위에 따른 예후 - 신형진; 이강현; 곽영수; 김선휴; 김현; 황성오 (Daehan oe'sang haghoeji, 2009)
Purpose: Computed tomography (CT) is an accurate test for evaluating hemodynamically stable patients with blunt abdominal trauma. Until now, there have been few studies concentrating on the diagnostic and prognostic significance of the intravenous contrast extravasation (CE) site. We investigated the site of CE on abdominopelvic CT (APCT) and its effect on treating trauma patients and predicting the clinical outcome. Methods: The 50 patients admitted to our emergency department with blunt abdominal trauma showing CE on APCT from January 2004 to September 2006 were included in this study. Patients were prospectively collected, and medical records were reviewed and analyzed. The patients’clinical and lab findings, Focused Assessment with Sonography for Trauma (FAST) findings, CT findings were analyzed. CE sites were classified as intraperitoneal, retroperitoneal, and pelvic cavity and were correlated with post-treatment complications, mortality, and morbidity. Results: Of the 50 patients (mean age : 45±18years, 29 males, 21 females) included in our study, 33 patients died (66%). There was no correlation between CE site and ICU or total hospitalization duration (p=0.553, p=0.523). During the first 24 hours of resuscitation, the pelvic cavity group required a mean of 20 units more of packed red blood cell (pRBC) transfusion compared to other groups (p=0.003). In the intraperitoneal group, more patients received operative invasive intervention - either laparotomy or embolization (p=0.025). The intraperitoneal group had the highest mortality, with 13 deaths (11/33, 39%), and the highest early mortality rate (10/13, 76%) in the first 24 hours (p=0.001). Conclusion: Intraperitoneal CE on the CT scan in cases of blunt abdominal trauma is regarded as an indication of a need for invasive intervention (either angiography or laparotomy) and of a higher mortality rate in the first 24 hours. A pelvic cavity CE rquires more aggressive transfusion with pRBC. However, the CT findings themselves showed no significant correlation with overall mortality, morbidity, or hospitalization. Purpose: Computed tomography (CT) is an accurate test for evaluating hemodynamically stable patients with blunt abdominal trauma. Until now, there have been few studies concentrating on the diagnostic and prognostic significance of the intravenous contrast extravasation (CE) site. We investigated the site of CE on abdominopelvic CT (APCT) and its effect on treating trauma patients and predicting the clinical outcome. Methods: The 50 patients admitted to our emergency department with blunt abdominal trauma showing CE on APCT from January 2004 to September 2006 were included in this study. Patients were prospectively collected, and medical records were reviewed and analyzed. The patients’clinical and lab findings, Focused Assessment with Sonography for Trauma (FAST) findings, CT findings were analyzed. CE sites were classified as intraperitoneal, retroperitoneal, and pelvic cavity and were correlated with post-treatment complications, mortality, and morbidity. Results: Of the 50 patients (mean age : 45±18years, 29 males, 21 females) included in our study, 33 patients died (66%). There was no correlation between CE site and ICU or total hospitalization duration (p=0.553, p=0.523). During the first 24 hours of resuscitation, the pelvic cavity group required a mean of 20 units more of packed red blood cell (pRBC) transfusion compared to other groups (p=0.003). In the intraperitoneal group, more patients received operative invasive intervention - either laparotomy or embolization (p=0.025). The intraperitoneal group had the highest mortality, with 13 deaths (11/33, 39%), and the highest early mortality rate (10/13, 76%) in the first 24 hours (p=0.001). Conclusion: Intraperitoneal CE on the CT scan in cases of blunt abdominal trauma is regarded as an indication of a need for invasive intervention (either angiography or laparotomy) and of a higher mortality rate in the first 24 hours. A pelvic cavity CE rquires more aggressive transfusion with pRBC. However, the CT findings themselves showed no significant correlation with overall mortality, morbidity, or hospitalization. KCI Citation Count: 0